Oxidative stress in ALS - Shaw, Pamela (Henry Stewart Talks, 2007)
Key facts, The normal human motor system, Motor neurone disease: clinical consequences, Spared motor neurone groups, Prognosis, Features of motor neurones which may underlie selective vulnerability, Complex and multifactorial disease, Genetic factors, SOD1 mutations, Potential mechanisms of neuronal oxidative stress, Sources of intracellular oxidative stress, Mitochondrial free radical production, ROS, Evidence for the role of oxidative stress in ALS, NSC34 cell model, G93A mutant SOD1, Oxidative stress in human ALS, Major pathogenetic factors, Glutamate, Excitotoxicity, Mitochondrial dysfunction, Potential mechanisms of action of antioxidant drugs, Clinical trials
Archived at 2018/05/31